Pattern of malocclusion in patients with noma sequelae: The need for orthodontic and orthognathic therapy - Mujtaba Bala; Ramat Oyebunmi Braimah; Abdurrazaq Olanrewaju Taiwo; Abubakar Abdullahi Bello; Muhammad Kaura Abubakar; Seidu Bello; Bandar Alyami; Rufai Jaafar; Ibrahim Abubakar Landi (Wolters Kluwer Medknow Publications, 2024)
Introduction: Noma is a gangrenous infection that destroys the orofacial structures and leaves the survivors with severe functional, psychosocial, and esthetic impairments. Malocclusion is one of the central sequelae that current Noma care often neglects. Aims: This study aimed to present the pattern of malocclusion in Noma survivors and highlight the role of orthodontic and orthognathic therapy in the management. Materials and Methods: This was a cross-sectional study conducted over 6 months. After obtaining institutional ethical approval, all noma survivors with permanent teeth, including complete upper and lower molars at least on one side, who presented for review were included in the study. Patients' demographics, Angle class of malocclusion, and various malocclusions were recorded. Data obtained were analyzed using the statistical package for the social sciences (IBM SPSS) version 25. Results: There were 35 (54.7%) males and 29 (45.3%) females in the age range of 12-36 years and a mean ± standard deviation of 22.52 ± 6.01 years. Most patients, 52 (81.3%), have Angle class 1 molar relation. Protrusion of anterior teeth was present in 34 (53.1%), posterior crossbite in 8 (12.5%), upper and lower teeth crowding in 11 (17.2%), isolated upper anterior crowding in 9 (16.7%), isolated lower anterior crowding in 4 (6.3%), and open bite in 5 (7.8%). Other dental malalignments, such as rotations and tooth displacement, were invariably present in 34 (53.1%). Conclusion: Malocclusion in noma survivors constitutes one of the most observable problems of noma sequelae. Orthodontic and orthognathic therapy could promote these patients' surgical, esthetic, and psychosocial rehabilitation.